Digital Competencies and Artificial Intelligence in Teaching and Learning English as a Foreign Language (Journal of the College of Basic Education, 2026)
Lifelong learning is crucial since knowledge is changing at such speeds that skills must be continuously mastered and reinforced. The challenge of artificial intelligence worries administrators because they think it will soon go from being a useful tool for human society to eventually taking over humanity. In education, artificial intelligence has altered the outmoded teacher - learner collaboration into one between a teacher or learner and artificial intelligence. This changeover necessitates a reconsidering of teachers' duties and the skills they request in the artificial intelligence era. However, few countries have well defined these competences or built nationwide programs to train teachers in artificial intelligence, leaving numerous educators lacking adequate supervision. Research indicates that artificial intelligence can provide benefits for teaching and learning English. Investigating the outcomes of AI's incorporation into education and the consequences it may have for institutions' futures is the aim of this study. It is an attempt to answer these questions: How is artificial intelligence being used for English language teaching and learning? What are the opportunities, issues, and challenges? The findings indicate that the integration of AI in education will provide new products, advantages, and disadvantages for educators and educational institutions.